2017
DOI: 10.3892/etm.2017.5488
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life on the clinical course of patients with chronic hepatitis C receiving daclatasvir/asunaprevir therapy: A prospective observational study comparing younger (<70) and elderly (≥70) patients

Abstract: Abstract. Interferon-free direct acting antiviral agent regimens for chronic hepatitis C (CHC) have been developed. These regimens have shown a high rate of sustained virologic response (SVR), and a reduction in side effects during treatment is also anticipated. However, the impact of the regimens on health-related quality of life (HRQOL) and side effects during treatment is not fully understood. The purpose of the present study was to evaluate HRQOL in the clinical course of patients with CHC receiving daclat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Different studies in different countries have investigated HRQoL and affecting factors in different contexts. The results of these studies can be helpful for health policy makers to determine the status of HRQoL and affecting factors in order to better planning of physical and mental health programs in societies (Lee et al, 2018;Raymakers et al, 2018;Ohashi et al, 2018). In a similar way, some studies in Iran have tried to measure HRQoL to provide evidence about determinants of HRQoL among general and specific groups such as patients and elderlies ( Jalali-Farahani et al, 2017;Hajian-Tilaki et al, 2017;Rezaei, Karami Matin, Kazemi Karyani, Woldemichael, Khosravi, Khosravipour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies in different countries have investigated HRQoL and affecting factors in different contexts. The results of these studies can be helpful for health policy makers to determine the status of HRQoL and affecting factors in order to better planning of physical and mental health programs in societies (Lee et al, 2018;Raymakers et al, 2018;Ohashi et al, 2018). In a similar way, some studies in Iran have tried to measure HRQoL to provide evidence about determinants of HRQoL among general and specific groups such as patients and elderlies ( Jalali-Farahani et al, 2017;Hajian-Tilaki et al, 2017;Rezaei, Karami Matin, Kazemi Karyani, Woldemichael, Khosravi, Khosravipour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes of HCV treatment have improved substantially with the emergence of direct-acting antiviral (DAA) agents, which are associated with nearly 100% sustained virologic response (SVR) or HCV cure, defined as absence of detectable virus 12 weeks after therapy completion, convenient dosing, and few side effects (5). Sustained virologic response has been shown to improve quality of life (6)(7)(8) and to lengthen survival (9)(10)(11).…”
mentioning
confidence: 99%
“…In addition, the nutritional status and liver fibrosis were improved in these patients and, therefore, the authors concluded that DAAs can induce long-term improvements in quality of life. Quality of life was assessed at three time points: before starting treatment, and at 12 and 24 weeks after completion of treatment [24].…”
Section: Discussionmentioning
confidence: 99%